If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.25(2c + -1) = 3c + -2 Reorder the terms: 1.25(-1 + 2c) = 3c + -2 (-1 * 1.25 + 2c * 1.25) = 3c + -2 (-1.25 + 2.5c) = 3c + -2 Reorder the terms: -1.25 + 2.5c = -2 + 3c Solving -1.25 + 2.5c = -2 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. -1.25 + 2.5c + -3c = -2 + 3c + -3c Combine like terms: 2.5c + -3c = -0.5c -1.25 + -0.5c = -2 + 3c + -3c Combine like terms: 3c + -3c = 0 -1.25 + -0.5c = -2 + 0 -1.25 + -0.5c = -2 Add '1.25' to each side of the equation. -1.25 + 1.25 + -0.5c = -2 + 1.25 Combine like terms: -1.25 + 1.25 = 0.00 0.00 + -0.5c = -2 + 1.25 -0.5c = -2 + 1.25 Combine like terms: -2 + 1.25 = -0.75 -0.5c = -0.75 Divide each side by '-0.5'. c = 1.5 Simplifying c = 1.5
| 3b+1=28 | | 0.06(a+200)+0.01a=172 | | x/9-9=8 | | 3(x+5)+4(x-3)+-6x=4 | | (8x^2-7x+2)+(3x^2-9x-6)= | | 2(x-4)+x-y=2y-9 | | -8(x-7)-9=47 | | 2(s+6)+2(s-1)+-4=74 | | (5z-9)(8+z)=0 | | x/3=4x/21-7 | | 60x-50=15x-5 | | x/3=4x/21 | | 13-4y+1y= | | 3(m+3)+5(m+1)+-6m=50 | | m=40 | | 6x+3(-3x-7)=0 | | 5x+15=x-20 | | 9xsquared-21=0 | | X-6-x-4=10-c | | -104=5x-3(5x+8) | | .5f=c+6u | | -3+5(b+4)+4(b+3)=2 | | x^(-3/5)=27 | | -7x-6(2x+5)=84 | | 3(n+3)+-2n+2(n+4)=65 | | 8-5x=2c-9x | | 16l=4c^2+9 | | -x/6=5-8 | | 12(t+2)+-7t+-8=6 | | 5x=48+x | | 6sec(x)+8=-4 | | 38.00=0.12m+8 |